2006
DOI: 10.1158/1078-0432.ccr-05-1418
|View full text |Cite
|
Sign up to set email alerts
|

A Novel One-Armed Anti-c-Met Antibody Inhibits Glioblastoma Growth In vivo

Abstract: Purpose: Expression of the receptor tyrosine kinase c-Met and its ligand scatter factor/ hepatocyte growth factor (SF/HGF) are strongly increased in glioblastomas, where they promote tumor proliferation, migration, invasion, and angiogenesis.We used a novel one-armed anti-c-Met antibody to inhibit glioblastoma growth in vivo. Experimental Design: U87 glioblastoma cells (c-Met and SF/HGF positive) or G55 glioblastoma cells (c-Met positive and SF/HGF negative) were used to generate intracranial orthotopic xenogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
221
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(231 citation statements)
references
References 29 publications
5
221
2
3
Order By: Relevance
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 95%
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 95%
“…In particular, a recent phase II clinical trial with MetMAb (onartuzumab, a one-armed antibody designed to compete with HGF by binding the extracellular portion of MET; ref. 73 ), conducted in patients with advanced NSCLC, has shown the clinical effi cacy of the combined therapy. This phase II study showed that patients whose tumors had high MET levels experienced a twofold increase in progression-free survival in response to MetMAb plus erlotinib compared with erlotinib alone.…”
Section: Clinical Translationmentioning
confidence: 99%
“…Xenografts derived from U87MG human glioblastoma cells, which activate MET by an autocrine mechanism (8), and H441 human lung cancer cells, which express phospho-MET (34), are sensitive to multitargeted kinase inhibitors (14,15,34). The growth of U87MG tumors is additionally impeded by ribozymes and antibodies directed at HGF (9,10) or MET (9,12). These data suggest that U87MG tumors depend on MET activity for their growth, but biologic agents targeting receptor tyrosine kinases can act via mechanisms other than inhibition of catalysis.…”
Section: Sgx523 Inhibits Met But Not Other Kinases In Cellsmentioning
confidence: 99%
“…In other malignancies, such as glioblastoma, autocrine activation of MET by HGF has been shown (8), and MET inhibition is effective in mouse models of glioblastoma (9)(10)(11)(12). The wealth of evidence linking MET to cancer has motivated efforts, using various strategies, to inhibit MET signaling (5,(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%